Vowel harmony and positional variation in Kyrgyz. Issue 1 (31st December 2020) - McCollum, Adam G.
While it is well known that the phonetic realization of a segment may differ by position, it is unclear how positional variation interacts with vowel harmony, the imperative that vowels be identical along some phonological dimension. Pearce (2008, 2012 ) contends that phonological harmony blocks phonetic reduction, suggesting that phonology dictates phonetic realization for this class of assimilatory patterns. This paper investigates harmony and vowel reduction in Kyrgyz, finding that non-initial vowels are more centralized than their initial-syllable counterparts. The potential sources for this reduction, including initial strengthening, supralaryngeal declination, predictability, and undershoot are discussed. The proposed predictability-based analysis provides an analysis of reduction based on phonological knowledge and representations.